On the Interpretation of Professor Leontief's System - Klein, L. R. (Review of Economic Studies, 1952)
Journal Article On the Interpretation of Professor Leontief's System Get access L. R. Klein L. R. Klein Michigan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 2, 1952, Pages 131–136, https://doi.org/10.2307/2295846 Published: 01 January 1952